Trichosporon beigelii peritonitis associated with continuous ambulatory peritoneal dialysis - Lopes, Jorge O.; Alves, Sydney H.; Benevenga, Jeni P.; Rosa, Antonio C.; Gomez, Vera C. (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
This paper reports a case of peritonitis caused by Trichosporon beigelii in a woman submitted to continuous ambulatory peritoneal dialysis. Diagnosis was established by direct examination and culture of dialysis effluent.